The Assessment of Mongolian Sovereign Funds (Mongolian Journal of International Affairs, 2020)
Mongolia is the one of the resource rich countries facing natural resource curse, relatively transparent with satisfactory resource governance. Some would argue establishing sovereign wealth fund (SWF) is beneficial those countries with natural resource curse while others against it. Mongolian government established several SWFs and namely Human Development Fund (HDF- afterwards renamed as Future Heritage Fund) and Fiscal Stability Fund (FSF) but still facing to create an efficient SWF. Some scholars would agree that it is important to find causal relations between management of SWF and its efficiency to establish an efficient and beneficial SWFs. There are several ways to reveal such relations, however, most research centres are using following major methods such as Resource Governance Index (RGI), Truman scoreboard and Linaburg- Maduell Transparency Index (LMTI) and Santiago Principles. This paper is examined Mongolian SWFs namely Human Development Fund (HDF) and Fiscal Stability Fund (FSF) using some of these methods.